PERSEPSI SISWA TENTANG MANIFESTASI TUGAS-TUGAS PERKEMBANGAN REMAJA SISWA KELAS XI SMA.NEGERI 11 SAMARINDA - MERLY HANDAYANI (fakultas Ushuluddin dan Dakwah IAIN Bone, 2020)
AbstractYouth development tasks are tasks that arise at or around a certain period of individual life, but in reality not all students are familiar with developing youth development tasks. The formulation of the problem in this study is